Strengthening Part Iii & Iv of Constitution @ 75 Years: A Reflection of Equality and Justice for All Genders - Madhav, Rupesh Chandra; Gautam, Yogita (Journal of Neonatal Surgery, 2025)
The goal of the feminist movement is to treat all people equally, regardless of gender. Men and women must be treated equally in all areas of society. To achieve gender equality, several interrelated social, political, environmental, cultural and educational conditions must be met. Many people around the world are realizing that progress is impossible as long as half of the population is disabled. Women face a multiplicity of complex issues. Apart from these concerns, the status of women in many cultures around the world remains deplorable, as women have no say over their own bodies or the bodies of their children. Women have long been considered vulnerable in society due to their physical, mental, and economic limitations. We live in a patriarchal society, where women have always been treated as second-class citizens and subjected to various forms of oppression. Combination of male dominated society, vote bank politics and economic realities has led to a refusal, to question the clerics on their interpretation of the personal laws such as Shariah, Manu Smiti etc. But society is changing with more education and exposure. More and more women are talking about these things and people have started saying that there is a need to change in Personal Laws. Women are not ready to accept old practice like triple talaq, polygamy, ban on entry in religious places etc. In this Article Authors has explained the various judgments and Legislations for understanding the Journey of 75 years of the Constitution for the purpose of analyzing the development towards achieving the goal of gender justice